Comparison of the Spo2/Fio2 Ratio and the Pao 2/Fio2 Ratio in Patients with Acute Lung Injury or Acute Respiratory Distress Syndrome (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: ARDS; A ALI; pulse oximetry